(3EjSGZhLjs - (3GdCHgQj GdSeQbfOj, CKjQ GdOjf, GdeaVd Hf YeQ GdeaVd, J (B663 (3g`s
(3ChdgG (B:s
(3fMeO Gddg Ydi Jhajbg agPg QSGdI aj GdefWb ChQOfG ajgG eG jLH GSJMVGQg def HjOg TjA ef GdYdhe eSJYjfG HGddY eajV GdNjQ hGdLhO GjSGZhLj GddaX GdOGd HGdhVY jOd Ydi JeGe eG hVY dg (B...s
(3BNQgG (B:s
(3hGdNWGHI hg bjGS eDda ef ebOeGJ ebHhdI YfO TNU eYJbO ajg Ch eXfhfI hGdTYQ hgh bjGS eDda ef ebOeGJ JfHSW efgG GdfaS Ch JfbHV hGdeZGdWI hgj bjGS eDda ef ebOeGJ cGPHI THjgI HGdMb JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\279s
(3cTa GdXfhf (B1\206s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs